Vikings : an encyclopedia of conflict, invasions, and raids - Mueller-Vollmer, Tristan; Wolf, Kirsten, 1959- (Santa Barbara, California : ABC-CLIO, 2022)
"This single-volume encyclopedia covers the large scope of Viking conflicts, invasions, and raids throughout history, using thematic essays and A-Z entries to show how their story has unfolded over time"--
Includes bibliographical references (pages 293-300) and index.
Keywords: Vikings -- Encyclopedias; Civilization, Viking -- Encyclopedias